Cochlear Implantation in Advanced Otosclerosis: Rising to the Challenges of Surgery and Decision making - Sharma, Shalabh; Singh, Satinder; Gupta, Anandita; Lahiri, Asish Kumar; Wadhera, Meenakshi (Bangladesh Journal of Otorhinolaryngology, 2022)
Introduction: Cochlear implantation as well as stapedotomy followed by use of hearing aid are acceptable modes of surgically rehabilitating patients with far advanced otosclerosis. Surgical challenges of CI include difficulties associated with electrode insertion and facial nerve stimulation. Improvement in speech discrimination scores and overall satisfaction with stapedotomy and hearing aid use are reportedly poor in many patients, yet being a low cost procedure it may be used as initial management in a subset of patients. Case Report: 46 year old patient with diffuse confluent retrofenestral otoscerosis underwent cochlear implantation. He was mapped using behavioral thresholds as despite intracochlear electrode position no neural response was recordable per-operatively as well as in the postoperative period. Perimodiolar electrodes and sodium flouride therapy were used to overcome problems of FNS. 18 months post CI the patient has good audiologic outcomes (CAP 7) without any FNS. Conclusion: High resolution computed tomography, air bone gap and speech discrimination scores are important in formulating treatment plan in patients with far advanced otosclerosis. Early cochlear implantation can be considered in patients with poor speech discrimination scores and extensive cochlear lesions. Facial nerve stimulation can be prevented by adequate pre-operative planning. Bangladesh J Otorhinolaryngol 2022; 28(1): 112-117